Assessment of the internal nasal dimensions of individuals with cleft lip and/or palate and obstructive sleep apnea by computed tomography - Loureiro, Natalia Bortotti (2022)
Background: Obstructive sleep apnea (OSA) is characterized by intermittent obstruction of the upper airways. The literature suggests a trend of association between nasal obstruction and sleep-disordered breathing, since 50% of adults with OSA report nasal obstruction symptoms. Individuals with cleft lip and/or palate (CL/P) due to an altered nasal morphophysiology, constitute a group especially prone to OSA development. Aims: To evaluate nasal cavity volumes, perimeters, and cross-sectional areas (CSA) of individuals with CL/P and OSA or primary snoring, by tomographic image analysis, compared to individuals with OSA without CL/P (N-CL/P). Method: Participants were divided into two groups: G1) CL/P+OSA or primary snoring (n=11); and G2) CL/P+OSA (n=13). From cone-beam computed tomography, the nasal cavities were segmented and reconstructed using the ITK-SNAP 3.8.0 software. In the SpaceClaim software, the 3D geometries were then used for computed aided design (CAD) models development, aiming at measuring volumes, areas, and perimeters of this anatomical structure. Results: Nasal cavities total volume, from the nostril to the nasal valve region (V1), and from the nasal valve to the upper limit of the nasopharynx (V2), although smaller in the CL/P+OSA group, did not differed from the CL/P+OSA group (p>0.05). The CSA and the perimeter of the nasal valve regions also did not differ statistically between groups (p>0.05). Otherwise, the CSA, and perimeter of the upper limit of the nasopharynx were significantly increased in those with CL/P+OSA than in the CL/P+OSA group (p0.05). Conclusions: Nasal internal geometry of patients with CL/P and OSA did not present significant differences in relation to apneic patients without CL/P. The influence of larger cross-sectional areas and perimeters observed in the nasopharynx of patients with CL/P and OSA on sleep-disordered breathing will be the focus of future studies.